Clinical significance of ESR1 gene copy number changes in breast cancer as measured by fluorescence in situ hybridisation. Issue 2 (25th December 2012) - Lin, Ching-Hung; Liu, Jacqueline M; Lu, Yen-Shen; Lan, Chieh; Lee, Wei-Chung; Kuo, Kuan-Ting; Wang, Chung-Chieh; Chang, Dwan-Ying; Huang, Chiun-Sheng; Cheng, Ann-Lii
Abstract : Aims: The ESR1 gene encodes for oestrogen receptor (ER) α, which plays a crucial role in mammary carcinogenesis and clinical outcome in patients with breast cancer. However, the clinical significance of the ESR1 gene copy number change for breast cancer has not been clarified. Methods: ESR1 gene copy number was determined by fluorescence in situ hybridisation (FISH) on tissue sections. A minimum of 20 tumour cells were counted per section, and a FISH ratio of ESR1 gene to CEP6 ≥2.0 was considered ESR1 amplification. A ratio >1.2 but <2.0 was considered ESR1 gain. The ESR1 copy number was further measured by quantitative real-time PCR (Q-PCR) with ASXL2 as a reference. Results: FISH revealed ESR1 amplification in six cases (4.0%) and ESR1 gain in 13 cases (8.7%) from a total of 150 cases. ESR1 gain and amplification were more common in older patients (p<0.001), and correlated well with ER protein expression (p=0.03) measured by immunohistochemistry, and ESR1 copy number (p<0.001) measured by Q-PCR. Furthermore, the multivariate analysis revealed that ESR1 amplification was associated with a shorter disease-free survival (HR=5.56, p=0.03) and a shorter overall survival (HR=5.11, p=0.04). Conclusions: In general, the frequency of ESR1 amplification in breast cancer is low when measured by FISH in large sections. ESR1 gain and amplification in breast cancer may be associated with older age and poorer outcomes.